Spin Doctors: A Model and an Experimental Investigation of Vague Disclosure - Marvin Deversi; Alessandro Ispano; Peter Schwardmann (Center for Economic Studies and ifo Institute (CESifo), 2018)
Unfavorable news are often delivered under the disguise of vagueness. But are people sufficiently naive to be fooled by such positive spin? We use a theoretical model and a laboratory experiment to study the strategic use of vagueness in a voluntary disclosure game. Consider a sender who aims at inflating a receiver's estimate of her type and who may disclose any interval that contains her actual type. Theory predicts that when facing a possibly naive receiver, the sender discloses an interval that separates her from worse types but is upwardly vague. Senders in the experiment adopt this strategy and some (naive) receivers are systematically misled by it. Imposing precise disclosure leads to less, but more easily interpretable, disclosure. Both theory and experimental data further suggest that imposing precision improves overall information transmission and is especially beneficial to naive receivers. Our results have implications for the rules that govern the disclosure of quality-relevant information by firms, the disclosure of research findings by scientists, and testimonies in a court of law.
Keywords: D82; D83; C92; L15; D04; 330; communication; naivete; flexibility; regulation